Studi Deskriptif Praktek Kerja Industri Kompentensi Keahlian Desain Komunikasi Visual SMK N 5 Kota Bengkulu - Anah Anah; Rohiat Rohiat; Puspa Djuwita (Manajer Pendididikan, 2018)
Abstract : The purpose of this study was to description the management practices of industry (prakerin) in DKV skill competetion of vocational High School 5 of Bengkulu City: (1) to know the description of the planning Practice the Working Industrial (Prakerin) in DKV skill competetion of vocational High School 5 of Bengkulu, (2) to know the description of the implementation Practice the Working Industrial (Prakerin) in DKV skill competetion of vocational High School 5 of Bengkulu, (3) to know the description the evaluation of Practice the Working Industrial (Prakerin) in DKV skill competetion of vocational High School 5 of Bengkulu. The methode of this research is a qualitative descriptive study. The subjectts of this research were principals, vice principals, students and  taechers at Vocational High School 5 of Bengkulu, and DU/DI (user), using data collection techniques such as observation, interview and documentation study, analyzed using with reduction, data presentation, and conclusion. The results and conclusion the research showed that the: (1) planning has been implemented fairly well starting from the curriculum, work program, prakerin administration, financing, socialization, and student counselor teacher, (2) implementation of prakerin runs properly but some obstacles are found such as students having difficulties when operating new tools, lack of time discipline. (3) evaluation have been undertaken by prakerin activity providers ranging from assesment, student reports to evaluation. Evaluation results indicate the need for follow-up on some finding such as the need to involve DU/DI parties in relation to available facilities as a place of practice for student where the school difficulties in the procurement  of such facilities.                                                                                    Key words : skill competetion, working practice of industry (prakerin)